Parenting Styles and Academic Performance: The Role of Authoritative, Authoritarian, and Permissive Parenting - Lamichhane, Basu Dev; Pradhan, Kohishma; Dangol, Sunita; Kandel, Pratikshya (Nepalese Journal of Business and Management Studies, 2024)
Available with full text.